2018
DOI: 10.3390/microorganisms6010009
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Management of Pseudomonas aeruginosa Bloodstream Infection Non-Susceptible to Carbapenems but Susceptible to “Old” Cephalosporins and/or to Penicillins

Abstract: It is unknown as to whether other beta-lactams can be used for bloodstream infections (BSI) resulting from Pseudomonas aeruginosa (PA) which are non-susceptible to one or more carbapenem. We conducted a retrospective cohort study at the Assaf Harofeh Medical Center (AHMC) from January 2010 to August 2014. Adult patients with PA-BSI non-susceptible to a group 2 carbapenem but susceptible to ceftazidime or piperacillin (with or without tazobactam), were enrolled. We compared the outcomes of patients who received… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…Zaidenstein et al reported sixty-seven Car-R/Ceph-S bloodstream infections from monobacterial clinical syndromes over a 5-year period (2010-2014). The authors have noted that in these cases, cephalosporins were considered as relevant therapeutic options [236]. Tsai et al characterized n = 14 P. aeruginosa isolates, that were resistant to carbapenems only.…”
Section: Carbapenem-resistant But Cephalosporin-susceptible P Aerugimentioning
confidence: 99%
See 1 more Smart Citation
“…Zaidenstein et al reported sixty-seven Car-R/Ceph-S bloodstream infections from monobacterial clinical syndromes over a 5-year period (2010-2014). The authors have noted that in these cases, cephalosporins were considered as relevant therapeutic options [236]. Tsai et al characterized n = 14 P. aeruginosa isolates, that were resistant to carbapenems only.…”
Section: Carbapenem-resistant But Cephalosporin-susceptible P Aerugimentioning
confidence: 99%
“…Even though there is growing literature available on the topic, there is no consensus on the most common mechanisms of resistance contributing to the emergence of Car-R/Ceph-S isolates. There are wide-ranging differences in the prevalence of carbapenemases (especially for MBLs), and this may affect the susceptibility to cephalosporins as well [73,[230][231][232][233][234][235][236][237][238][239][240][241][242][243][244]. Khalili et al proposed that the detection of Car-R/Ceph-S isolates is dependent on the absence of carbapenemases [240].…”
Section: Carbapenem-resistant But Cephalosporin-susceptible P Aerugimentioning
confidence: 99%
“…Most of these bacteria had reduced oprD gene expression levels, while AmpC hyperproduction, carbapenem hydrolysis (detected by the MALDI-TOF MS method) and efflux pump overexpression (RT-PCR) were not shown in these isolates. A recently published clinical study from Israel (corresponding to the time period between 2010 and 2014) reported n = 67 monobacterial Car-R/Ceph-S bloodstream infections (mainly associated with UTIs and pneumonia), where the authors highlighted that cephalosporins were relevant therapeutic options for these infections [31]. In addition, a study from Iran identified n = 23 Car-R/Ceph-S P. aeruginosa isolates from 243 clinical samples, from the time period between 2016 and 2018 [14].…”
Section: Discussion and Literature Reviewmentioning
confidence: 99%
“…Thus, clinicians may consider the use of ceftazidime, cefepime, or piperacillin-tazobactam against these P. aeruginosa isolates. Some studies suggested that non-carbapenem-beta-lactams (ceftazidime, piperacillin, and/or piperacillin-tazobactam) may still be effective alternatives for short-course therapy for BSI caused by P. aeruginosa strains, but should be used with caution in high-inoculum infections such as endocarditis and osteomyelitis [11,12].…”
Section: Discussionmentioning
confidence: 99%